Partial blind signature scheme based on SM9 algorithm - Yao LYU; Jinpeng HOU; Chong NIE; Mang SU; Bin WANG; Hongling JIANG (网络与信息安全学报)
Ordinary digital signatures have many deficiencies in effectively protecting users' privacy, and signature repudiation and tracking occur from time to time.In order to solve the above problems, a partial blind signature scheme based on the SM9 algorithm was proposed.Partially means that the signature message contains the user's message and other related information, so it can effectively resist signature repudiation and tracking, and introduce a trusted third party to prevent malicious users from tampering with information.Through experimental results and theoretical analysis, the security and efficiency of the proposed algorithm are proved.